Sistema de Avaliação da Educação Básica (Saeb): trajetória e alterações no período de 1990 a 2021 - Magalhães, Wesley Brito (2022)
This master's thesis was developed with the Graduate Program in Education (PPGE) of the Fac-ulty of Education of the Federal University of Goiás (FE/UFG) and is linked to the research line State, Policies, and History of Education. This is a study on Brazil's first and longest-running large-scale external national assessment: the Basic Education Assessment System (Saeb), which corresponds to a set of assessments carried out periodically through the application of cognitive and questionnaires for specific stages of basic education. Over its more than thirty years of existence, Saeb has undergone several changes that shows a vicious circle in politics. From this perspective, the general objective of the research was to identify, describe and ana-lyze the historical trajectory of Saeb, with emphasis on changes in methodological formats and resulting educational implications. The research was guided by the following specific objectives: a) Identify and characterize the social, political, and economic context that made evaluation one of the structuring axes of educational policies, based on the concept of neoliberalism; b) Identify and analyze the purposes of Saeb and its relationship with other educational policies, from its creation to the present day; c) Identify and problematize the concepts of educational quality present in the Saeb in contrast to the socially referenced quality perspective. Adopting a qualitative approach as a methodological framework, this research is of a descriptive-analyt- ical nature, based on a bibliographic survey and documental research. The exhibition is theo-retically based on reference authors in the field of evaluation, among them: Afonso (2009), Dias Sobrinho (2003), Gatti (2013), Freitas D. (2013), Freitas L. (2013), Horta Neto (2018), Sousa (2020), among others, and is divided into three chapters. The first chapter highlights that ne-oliberal thought submits society to competitive dynamics, by inserting the market logic into all social relations and all spheres of life, both objective and subjective, in the case of education, inserting market mechanisms through of external and large-scale evaluations. The second chap-ter describes and analyzes the historical trajectory of the policy, highlighting its changes and its influence on other educational policies, such as the PNE 2014-2024, the BNCC, and the new Fundeb, as well as its presence in the National Evaluation Policy. The third chapter discusses the concepts of accountability in education, evaluation culture, equity, efficiency, and quality, present in Saeb's objectives, with emphasis on the last one, the target of constant disputes and discourses: on the one hand, the managerial quality and on the other, the social, which takes into account a multiplicity of intra and extra-school factors that permeate the educational pro-cess. It is concluded that the constant changes of Saeb throughout its period of validity config-ure a vicious circle of "more of the same", and contribute to reaffirming, intensifying and con-solidating a logic of educational management guided by the control of results, with a regulatory purpose, classification, and competition, and that this policy does little to address the situation of inequalities in Brazilian education.